MARKET ORIENTATION: COMPANY PERFORMANCE AND GLOBAL CONSUMER CULTURE CHANGE - Stanny S. Rawung (Journal of International Conference Proceedings (JICP), 2019)
Market orientation (market orientation) is a measure of behavior and activity that reflects the implementation of the marketing concept. Ironically, although the marketing concept has been developed in the decade of the 1950s, it was only in the 1990s that empirical studies began to be conducted to examine the marketing concepts of business strategy and success. In line with the development of the business world today a term "Global Village" was born stating that a mechanism of world trade is described as a market in a village. The concept of thought is translated as an increasingly smaller market phenomenon with the support of technological advances and information as factors important for companies to be able to innovate, adapt and respond automatically to consumers. International marketing is one activity that is in line with Global Village thinking. In accordance with the development of increasingly global information technology, global consumers also experience developments in terms of culture. Because culture is attached to consumers which is a major factor in international trade. This study aims to analyze more deeply the relationship between market orientation and company performance and changes in global consumer culture. The research method used in the study was a qualitative approach with analytical techniques using the Miles and Huberman models. The data used in this study are secondary data that have been officially published through articles and other studies that relate to the topics that are the focus of research.